God Does Not Play Dice with the Universe, or Does He?: Anthropological Interlocutions of Sport and Religion - Carter, Thomas F. (Religion and society, 2012)
Religion has been a central object of anthropological inquiry since its earliest days. In contrast, sport has remained an ancillary object of interest at best. Nonetheless, anthropologists have written some provocative analyses that challenge other disciplinary approaches to sport. Principally, those analyses emerged out of anthropological approaches to religion. Concerned with the ways in which anthropology theorizes and analyzes both religion and sport, this article begins by assessing the modern-day myth that 'sport is a religion'. It then compares subject-specific approaches to the relationships between sport and religion. The article then moves to the anthropological focus on ritual as it developed in the study of religion and how those ideas were then applied to analyses of sport. The article concludes with an examination of how the anthropology of sport has moved beyond those initial efforts before discussing various anthropological approaches to sport and religion.